Annual Monitoring Report on Integration 2012 - KINGSTON, GILLIAN; QUINN, EMMA; MC GINNITY, FRANCES; O'CONNELL, PHILIP J. (ESRI/The Integration Centre)
This year?s Annual Monitoring Report on Integration 2012, launched today, uses a range of indicators to measure different aspects of immigrant inclusion in Irish society. Key Findings: The consistent poverty rate among Non-EU nationals, at over 12%, is almost twice as high as amongst Irish nationals (just over 6%) in 2010, and the gap between Irish and non-EU nationals has widened since 2008. [Consistent poverty is defined as a combination of having a low income and lacking two basic items such as food, clothes or home heating] . Almost one third of first-generation immigrants aged 15 scored below the basic level (1) of English reading proficiency in the Programme for International Student Assessment (PISA) tests (2009). This compares to almost 1 in 6 of Irish 15-year-olds. At the start of 2012 the unemployment rate was 18.5% among non-Irish nationals, compared to just under 15% for Irish nationals. Overall non-Irish nationals have been harder hit in the labour market by the current recession than Irish nationals. During 2011, 9,500 nationals of countries outside the European Economic Association (EEA) acquired Irish citizenship, compared to just under 5,000 in 2010.
PUBLISHED
Keywords: Integration